Description of development of fear arousal message in smoking cessation video - Nurumal, Mohd Said; Azmi, Junainah; Nik Mohamed, Mohamad Haniki; Ab Rahman, Norny Syafinaz; Firdaus, Mohd Khairul Zul Hasymi; Che Hasan, Muhammad Kamil; Jamaludin, Thandar Soe Sumaiyah (2020)
This research sought to evaluate the effectiveness of fear arousal message in smoking cessation program among cardiovascular disease patients. Another primary focus of this research was to identify the predicting factors of smoking cessation in the study. A total of 65 adult smokers (31 in the control group and 34 in the intervention group) were purposively recruited from a cardiac unit in a non-profit government hospital in Malaysia. A testimonial video of a real life patient was specifically developed by the researcher for this interventional study. Elements of fear arousal message and self-efficacy were integrated into the video. A set of questionnaire consisted of socio-demographic status, smoking history, Patient’s stages of behavioral changes based on the Transtheoretical Model Questionnaire, and Patient’s Motivation to Quit Smoking Questionnaire. The primary measure in the study was the smoking status of the participants at a 3-month follow-up. The intervention group shows a significant improvement of motivation level from only 6.5% of the participants in the group were very strongly motivated at baseline to 54.8% at follow-up, with p=0.001. Overall, the total number of final quit rates in the intervention group were higher, where 41.9% of the participants in the group have quitted smoking at the twelve-week follow-up as compared to only 20.6% quit rate in the control group at the final follow-up. These results demonstrate the effectiveness of the intervention at least in the short-term study. Thus it is hoped that this new smoking cessation program will be a great benefit for future tobacco control program in our country. In addition, this new intervention can be integrated into the government policy and nursing practice to improve the cessation outcome especially for cardiac smokers in Malaysia.